Pengaruh Pembelajaran Steam (Science, Technology, Engineering, Art And Math) Terhadap Perkembangan Kognitif Anak Usia Dini - Prety Tamelab; Demarlin Talan; Amelia Lole; Delsia Ninurasa; Dicesya Bunga; Nofri Teflopo; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Cognitive development is a fundamental aspect in the formation of thinking and problem solving abilities in early childhood. This research aims to analyze the influence of STEAM learning on the cognitive development of children aged 3-5 years at PAUD Efata Liliba, Kupang City. The research method uses a quantitative approach. The research sample consisted of 15 children who were selected using a purposive sampling technique with the criteria that the children were actively involved in learning and were aged 3-5 years. The data collection instrument is a questionnaire sheet for STEAM learning and cognitive development. The data analysis technique is simple linear regression. The research results prove that STEAM learning has a positive and significant effect on children's cognitive development with a coefficient of determination (R²) of 91.6%. It is hoped that educators can implement STEAM learning in a consistent and structured manner, understand children's individual characteristics and needs, and provide learning media that supports exploration and creativity to optimize the stimulation of cognitive development in the early childhood learning process.